2005
DOI: 10.1159/000083166
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, Interhemispheric Transfer, and Right Hemispheric Specialization: A Critical Review

Abstract: Background: One neural model of alexithymia relates the condition to poor interhemispheric transfer, while another model associates it with a disturbance in right hemisphere activity. Methods: The available empirical evidence directly relating alexithymia to a deficit in interhemispheric transfer and/or in right hemisphere activity is critically reviewed. Results: The interhemispheric transfer studies have related alexithymia to a deficit in transfer, but the nature and directionality of the transfer deficit h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 90 publications
(103 reference statements)
5
37
0
Order By: Relevance
“…One potential explanation is that the three factors of alexithymia have different origins in depressed patients, as presented recently [23]. Also other biological explanations, like interhemispheric transfer or right hemispheric specialisation, for personality construct of alexithymia, have to be empirically studied [24]. …”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is that the three factors of alexithymia have different origins in depressed patients, as presented recently [23]. Also other biological explanations, like interhemispheric transfer or right hemispheric specialisation, for personality construct of alexithymia, have to be empirically studied [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence demonstrated that individual differences, for example, in temperament are associated with differences in brain and peripheral physiological functioning (see [13,7]). Findings from some studies suggest that alexithymia (less ability to identify and communicate feelings) could be investigated as a continuous personality trait associated with either the interhemispheric transfer of information [21] or the relative development and activation of the two hemispheres in non-clinical and clinical populations ( [22]; but see [23]) or as a syndrome related to some psychiatric disturbance such as Multiple Sclerosis. Therefore, individual differences in processing emotional stimuli provide a potentially rich source of information about the relationship between emotion and cognition, in normal people but also in individuals suffering from neurobiological impairment.…”
Section: Emotional Categorization: Individual Differences and Lateralmentioning
confidence: 99%
“…Recent works focused on alexithymia have proposed different hypotheses to explain it in structural and functional terms (see [23]). In structural terms, one neural hypothesis suggests that alexithymia is related to poor interhemispheric transfer, in normal as well as clinical populations [21,23,62].…”
Section: Emotional Categorization: Individual Differences and Lateralmentioning
confidence: 99%
See 2 more Smart Citations